The Effect of Renewable Energy, Eco-Efficiency, and Carbon Emission Disclosure on Firm Value - Alifa Salsabila Putri; Elysia Intan Nursafa; Christina Dwi Astuti (LifeSciFi, 2026)
Increasing attention is being paid to corporate value, which is influenced not only by financial performance but also by environmental sustainability practices such as renewable energy, eco-efficiency, and carbon emission disclosure. The purpose of this study is to analyze the effect of renewable energy, eco-efficiency, and carbon emission disclosure on corporate value in the basic materials manufacturing sector listed on the Indonesia Stock Exchange for the 2021–2025 period. This study uses a quantitative descriptive-explanatory approach using secondary data from annual reports and sustainability reports. The research sample consisted of 37 companies with 143 observations analyzed using multiple linear regression and classical assumption tests. The results show that renewable energy has no significant effect on corporate value, while eco-efficiency and carbon emission disclosure have a positive and significant effect on corporate value. Simultaneously, all three variables influence corporate value, although their explanatory power is relatively low. The conclusion of this study confirms that certain sustainability aspects, particularly environmental efficiency and emission transparency, play a significant role in improving market perceptions of companies. These findings provide implications for companies, investors, and regulators in strengthening sustainability strategies to sustainably increase corporate value in the future.